The Contribution of Transmission Electron Microscopy (TEM) to Understanding Pre‐Columbian Goldwork Technology. (26th April 2017) - Vindel, E.; García, J.; Gumiel, C.; López‐Acevedo, V.; Hernando, M.
Abstract : This paper highlights the contribution of transmission electron microscopy (TEM) when combined with scanning electron microscopy and energy‐dispersive X‐ray microanalysis (SEM/XEDS) to characterize objects in archaeology. The application of TEM in archaeology is not yet a common tool, but it may provide data that are significant to understanding pre‐Columbian gold metallurgy, specifically the gilding and silvering methods. Two gilded rods were studied using a combination of TEM and SEM/XEDS techniques. The objects were found at the Atacames archaeological site, in the Esmeraldas region, Ecuador, which was occupied betweenad 750 and 1526 by the Atacames culture. The microchemical and structural results of the inner and the external gilded part of the artefacts support the hypothesis of a gold diffusion to the surface enhanced by chemical treatment with chloride‐rich solutions, heating and successive annealing processes. The present study reveals that microstructural investigation by TEM provides useful information with which to investigate the techniques used to modify the chemical surface composition of pre‐Columbian artefacts.